PELAKSANAAN IKRAR TALAK DI HADAPAN SIDANG PENGADILAN AGAMA (Suatu Tinjauan Filsafat Hukum Islam) - Misra, Abustam (Pasca Sarjana STAIN Watampone, 2016)
In the wisdom of the implementation of the pledge before the divorce trial Religious